PELATIHAN ORIENTASI MASA DEPAN DAN HARAPAN KEBERHASILAN STUDI PADA SISWA SMA - Jembarwati, Otih (Universitas Ahmad Dahlan, 2015)
AbstractThe purpose of the study was to explore the influence of future orientation training on student’s future orientation improvement and relationship between future orientation and expectation for learning success. This study involved 37 of tenth grade students in one of private Senior High School in Semarang. The research used quantitative method with experiment approach and one group pre- test post-test design to test find out the difference between students’ future orientation before and after training and explore the correlation between students’ future orientation and expectation for student learning success.Result showed that there was a significant difference of future orientation before and after training, (Z = -5,304). Correlation analysis between future orientation and expectation for student’s learning success showed that there was relationship between future orientation and expectation for student’s learning success, with correlation r = 0.477.implication of these results for the study of future orientation and expectation for student’s learning success are exlpored.Keywords: future orientation, learning success expectation, training